2018
DOI: 10.4040/jkan.2018.48.4.465
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Hand Massage in Patients Who Underwent Transradial Percutaneous Coronary Intervention

Abstract: Hand massage can be a helpful nursing intervention for transradial percutaneous coronary intervention by reducing pain and discomfort to a considerable degree.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 14 publications
5
2
0
Order By: Relevance
“…Because elevating the upper body relieves pressure on the body and prevents spasticity (Cha & Sok, 2016), it is considered an effective procedure to relieve physical discomfort. In addition, previous studies by Kim et al (2008) and Shin and Kim (2018) in patients undergoing percutaneous coronary intervention found that the patients' physical discomfort was reduced after offering a hand massage, similar to the findings of our study.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Because elevating the upper body relieves pressure on the body and prevents spasticity (Cha & Sok, 2016), it is considered an effective procedure to relieve physical discomfort. In addition, previous studies by Kim et al (2008) and Shin and Kim (2018) in patients undergoing percutaneous coronary intervention found that the patients' physical discomfort was reduced after offering a hand massage, similar to the findings of our study.…”
Section: Discussionsupporting
confidence: 92%
“…In addition, previous studies by Kim et al ( 2008 ) and Shin and Kim ( 2018 ) in patients undergoing percutaneous coronary intervention found that the patients' physical discomfort was reduced after offering a hand massage, similar to the findings of our study. Hand massage is effective in alleviating discomfort because it relaxes muscles and increases blood circulation (Kim & Cho, 2012 ; Shin & Kim, 2018 ). Therefore, our study results can be considered of statistically significance to confirm that providing a combined intervention of 25° upper body elevation and hand massage to patients who have undergone RFCA with limited movement is effective in alleviating physical discomfort.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations